2012
DOI: 10.2340/00015555-1188
|View full text |Cite
|
Sign up to set email alerts
|

Psychoneuroimmunology of Psychological Stress and Atopic Dermatitis: Pathophysiologic and Therapeutic Updates

Abstract: Atopic dermatitis is a chronic inflammatory skin disease characterized by impaired epidermal barrier function, inflammatory infiltration, extensive pruritus and a clinical course defined by symptomatic flares and remissions. The mechanisms of disease exacerbation are still poorly understood. Clinical occurrence of atopic dermatitis is often associated with psychological stress. In response to stress, upregulation of neuropeptide mediators in the brain, endocrine organs, and peripheral nervous system directly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(62 citation statements)
references
References 153 publications
(176 reference statements)
0
59
0
3
Order By: Relevance
“…We have previously reported that ATP and a hydrolysis-resistant, long-lived analog of ATP, ATPγS, enhance secretion of IL-6 and the chemokines CXCL8, CCL2 and CXCL1 by HMEC-1 cells and pHDMECs [54, 55]. Sympathetic nerve influences on expression of inflammatory factors by dermal microvascular endothelial cells may be of particular interest as inflammatory skin diseases including psoriasis, atopic dermatitis, acne and rosacea are all believed to be exacerbated by stress [20, 29–31, 33, 7779]. We have hypothesized that under conditions of stress, the SNS is activated and sympathetic nerves associated with dermal vessels release ATP, which then enhances the inflammatory functions of endothelial cells, resulting in increased cutaneous inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that ATP and a hydrolysis-resistant, long-lived analog of ATP, ATPγS, enhance secretion of IL-6 and the chemokines CXCL8, CCL2 and CXCL1 by HMEC-1 cells and pHDMECs [54, 55]. Sympathetic nerve influences on expression of inflammatory factors by dermal microvascular endothelial cells may be of particular interest as inflammatory skin diseases including psoriasis, atopic dermatitis, acne and rosacea are all believed to be exacerbated by stress [20, 29–31, 33, 7779]. We have hypothesized that under conditions of stress, the SNS is activated and sympathetic nerves associated with dermal vessels release ATP, which then enhances the inflammatory functions of endothelial cells, resulting in increased cutaneous inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to similar psychophysiological changes (24) and reported comorbidity of anxiety and allergy (16,17,18,23) as well as the role of stress in allergic process (15), psychological interventions aimed on better coping and reduction of anxiety could be beneficial to allergic patients (45). Similarly, interventions based on normalization of HRV such as HRV biofeedback might also be employed, which has already been demonstrated in a study with asthma (46).…”
Section: Clinical Relevance Of the Resultsmentioning
confidence: 90%
“…Current neuroendocrinology research on allergy underlines the importance of psychological factors, such as stress, in the onset and pathogenesis of allergies (15). Cumulative allostatic load may play a part in allergic inflammatory process as well as changes in psychological states, e.g.…”
Section: Anxiety and Allergymentioning
confidence: 99%
“…This results in increased humoral immunity through the action of cytokine IL4. This leads to activation of B cells and increases the activity of eosinophils through cytokine IL5 (53). The induction and maintenance of eosinophils is performed by Th2 cytokines.…”
Section: Neuro-endocrine Pathway In the Genesis Of The Diseasementioning
confidence: 99%
“…The major stressors related to chronic skin conditions are: itching, sleep disturbance, withdrawal of touching, fear of allergies, changes in diet, psychosexual problems and others (53). The influence of these factors depends on individual and generic characteristics.…”
Section: Neuro-endocrine Pathway In the Genesis Of The Diseasementioning
confidence: 99%